Incidence of adverse cardiovascular events associated with immune checkpoint inhibitors and risk factors for left ventricular dysfunction: A single-center prospective clinical study - Zhang, Chuan; Chen, Zhulu; Qin, Shu; Zhu, Yuxi; Shu, Linjie; Zuo, Zhong (Frontiers in Cardiovascular Medicine, 2023)
Background The incidence of immune checkpoint inhibitors (ICI)-related adverse cardiovascular events (ACEs) may be underestimated, and there are few reports on the incidence and risk factors of ICI-induced left ventricular dysfunction (LVD). Objectives This study aimed to investigate the incidence of ACEs caused by ICI, in particular to analyze the incidence and risk factors of LV systolic and diastolic dysfunction. Materials and methods A prospective clinical study was performed on patients who received ICI in our hospital from November 2020 to October 2021. They received regular cardiovascular examinations, including echocardiography, ECG, cTnT, and NT-proBNP, etc. The incidence of various ACEs was counted, and the risk factors of LVD were analyzed. Results A total of 106 cancer patients treated with ICI were recruited. During the follow-up, 41 patients (38.68%) developed various ECG abnormalities, 39 patients (36.79%) developed LVDD, 9 patients (8.49%) developed CTRCD, and 2 patients (1.89%) developed new pericardial effusion. The patients with elevated cTnT, CK-MB, and NT-proBNP were 10 (9.43%), 8 (7.55%), and 8 (7.5%), respectively. Thirteen of the 52 patients with LVD had hypertension, while 4 of the 54 patients without LVD had hypertension (OR = 4.17, 95% CI: 1.26–13.78; P = 0.019). The baseline LVEF and LVFS of patients with LVD were 61.54 ± 4.15% and 33.78 ± 2.73%, while those of the control group were 64.16 ± 3.68% and 34.95 ± 2.84, respectively (P = 0.003 and P = 0.048). Compared with patients without LVD, patients with LVD had lower e’ (6.99 ± 1.33 cm/s vs. 7.64 ± 1.39 cm/s, P = 0.029) and higher E to e’ ratio (11.89 ± 3.15 cm/s vs. 10.43 ± 2.52, P = 0.024). Multiple regression analysis showed that a history of hypertension (HR = 26.52, 95% CI: 2.479–283.667, P = 0.007) and lower baseline e’ (HR = 0.04, 95% CI: 0.003–0.709, P = 0.028) were risk factors for developing LVD. Conclusion Patients treated with ICI may develop multiple ACEs, including acute myocarditis, pericarditis, ECG abnormalities, and elevated cardiac biomarkers. ICI may lead to a high incidence of LVD, and echocardiography is helpful for early detection of LVD. Patients with hypertension or poor LV systolic or diastolic function at baseline were predictors of LVD after ICI treatment.